Causal and observational evidence on the role of early menopause in hypertension. (14th October 2021) - Roa Diaz, Z M; Asllanaj, E; Amin, H A; Rojas, L Z; Nano, J; Ikram, M A; Drenos, F; Franco, O H; Pazoki, R; Marques-Vidal, P; Voortman, T; Muka, T
Abstract: Introduction: Blood pressure has been suggested as potential factor contributing to the increased risk of cardiovascular disease observed in women experiencing early menopause (<45 years). However, whether the association between early menopause and hypertension is causal remains unclear (1, 2). Purpose: To evaluate the observational and causal association between age at natural menopause (ANM) and blood pressure (BP) traits in Caucasian women. Methods: Cross-sectional and one-sample Mendelian randomization (MR) study was conducted in 4451 postmenopausal women from two different cohort studies. Hypertension was defined as a systolic BP (SBP) ≥140 mmHg, and/or diastolic BP (DBP) ≥90 mmHg, and/or the use of antihypertensive medication. Multivariable linear and logistic regressions were implemented in the observational analysis. We calculated a weighted genetic risk score with 54 variants associated with ANM (GRS-ANM) (3). The genetic variants were previously identified in a genome wide association study (4), after that we implemented two-stage least squares in the one-sample MR. Estimates from all cohorts were pooled through meta-analysis Results: The pooled analysis across cohorts showed early menopause, compared to menopause between 50–54 years, to be associated with lower DBP (β=−1.31 mmHg, 95% CI: −2.43; −0.18), while no association was found between other ANM categories and DBP. Similarly, the pooled analysis of both cohorts did not show an association of ANM with SBP, neither as a continuous variable nor by category. One year of later onset of menopause was associated with higher odds of developing hypertension (Odds ratio (OR): 1.02, 95% CI: 1:00; 1.04) while no association was found for the ANM categories and hypertension (Table 1). Results of the evaluation of MR assumption, supported their compliance, the GRS-ANM was associated with observed ANM and explained between 1.4% and 3.4% of the ANM variance in the included cohorts, F statistic values were among 11.15 and 40.63 (Figure 1). We found no association between GRS-ANM and SBP, DBP or hypertension (Table 1). Conclusion: The present study does not support the hypothesis that early onset of menopause is associated with higher BP. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): The CoLaus study was and is supported by research grants from GlaxoSmithKline, the Faculty of Biology and Medicine of Lausanne, and the Swiss National Science Foundation (grants 33CSCO-122661, 33CS30-139468 and 33CS30-148401).Zayne M. Roa-Díaz has received funding from the European Union's Horizon 2020 research and innovation programme under the Marie Skłodowska-Curie grant agreement No 801076, through the SSPH+ Global PhD Fellowship Programme in Public Health Sciences (GlobalP3HS) of the Swiss School of Public Health.